A systematic literature review of societal acceptance and stakeholders' perception of hydrogen technologies. (1st September 2021) - Emodi, Nnaemeka Vincent; Lovell, Heather; Levitt, Clinton; Franklin, Evan
Abstract: This paper presents the results of a systematic review that analysed the literature on factors influencing societal acceptance and stakeholders' perceptions of hydrogen related technologies. This study found that the most influencing factors include prior knowledge, perceived cost/risks, environmental knowledge, higher education and income, personal and distributive benefits, infrastructure availability and close proximity to hydrogen facilities. There was low hydrogen awareness in more than 60% of the countries analysed in the reviewed studies. Although stakeholders had diverse perceptions, there was agreement that infrastructure availability, affordability, local community engagement, regional skill capability development, preservation of biodiversity, and safety and distributive benefits to the community were essential for a successful hydrogen industry. Future research could examine consumer acceptance at different geographical scales, analyse pre-and post-hydrogen project implementation, and social impact of hydrogen infrastructure on local communities. We also recommend diversifying hydrogen research projects and investigating the policy and regulatory arrangements for community-owned hydrogen projects. Highlights: Acceptance papers are dominated by Western European studies. Prior knowledge, perceived cost, risks and benefits are among acceptance factors. There was low hydrogen awareness in more than 60% of the countries analysed. Community engagement, infrastructure availability and safety are common perceptions. Few post-hydrogen implementation surveys and dynamic social analysis.